2022
DOI: 10.3390/biom12020253
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with the Assembly Chaperone Ump1 Promotes Incorporation of the β7 Subunit into Half-Proteasome Precursor Complexes Driving Their Dimerization

Abstract: Biogenesis of the eukaryotic 20S proteasome core particle (PC) is a complex process assisted by specific chaperones absent from the active complex. The first identified chaperone, Ump1, was found in a precursor complex (PC) called 15S PC. Yeast cells lacking Ump1 display strong defects in the autocatalytic processing of β subunits, and consequently have lower proteolytic activity. Here, we dissect an important interaction of Ump1 with the β7 subunit that is critical for proteasome biogenesis. Functional domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The most consistent and sizable truncations occur within β5 and β7 propeptides (Fig. 6c ), which recruit β6 and promote proteasome dimerization via interactions with Ump1, respectively 61 , 62 . Contrary to the tendency towards reduction, many microsporidians have expanded their β6 propeptides by >70 amino acids.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The most consistent and sizable truncations occur within β5 and β7 propeptides (Fig. 6c ), which recruit β6 and promote proteasome dimerization via interactions with Ump1, respectively 61 , 62 . Contrary to the tendency towards reduction, many microsporidians have expanded their β6 propeptides by >70 amino acids.…”
Section: Resultsmentioning
confidence: 94%
“…The propeptides of the β subunits are also frequently modified. These segments are integral to the assembly process, where they protect catalytic residues and recruit other subunits and assembly factors 61 , 62 . The most consistent and sizable truncations occur within β5 and β7 propeptides (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The most consistent and sizable truncations occur within β5 and β7 propeptides ( Fig. 6c ), which recruit β6 and promote proteasome dimerization via interactions with Ump1, respectively 55,56 . Contrary to the tendency to extreme reduction, many microsporidians have expanded their β6 propeptides by more than 70 amino acids.…”
Section: Resultsmentioning
confidence: 94%
“…The propeptides of the β subunits are also frequently modified. These segments are integral to the assembly process, where they protect catalytic residues and recruit other subunits and assembly factors 55,56 . The most consistent and sizable truncations occur within β5 and β7 propeptides ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CP formation by dimerization of two such complexes is triggered by incorporation of β7 subunits, the C-terminal extensions of which reach out to the respective other halves to stabilize the newly formed 20S particle [17,21]. Recently, we reported that β7 recruitment is promoted by an N-terminal domain of Ump1 that interacts with the β7 pro-peptide [22]. Upon maturation of the active sites by autocatalytic processing, the assembly chaperones Ump1 is degraded, and Pba1-Pba2 is released [9,19].…”
Section: Introductionmentioning
confidence: 99%